Aerodynamic ground effects on DLRF6 vehicle. Issue 5 (14th June 2021) - Tahani, Mojtaba; Masdari, Mehran; Bargestan, Ali
Abstract : Purpose: The overall performance of an aerial vehicle strongly depends on the specifics of the propulsion system and its position relative to the other components. The purpose of paper is this factor can be characterized by changing several contributing parameters, such as distance from the ground, fuselage and wing as well as the nacelle outlet velocity and analyzing the aerodynamic performance. Design/methodology/approach: Navier–Stokes equations are discretized in space using finite volume method. A KW-SST model is implemented to model the turbulence. The flow is assumed steady, single-phase, viscous, Newtonian and compressible. Accordingly, after validation and verification against experimental and numerical results of DLRF6 configuration, the location of the propulsion system relative to configuration body is examined. Findings: At the nacelle outlet velocity of V/Vinf = 4, the optimal location identified in this study delivers 16% larger lift to drag ratio compared to the baseline configuration. Practical implications: Altering the position of the propulsion system along the longitudinal direction does not have a noticeable effect on the vehicle performance. Originality/value: Aerial vehicles including wing-in-ground effect vehicles require thrust to fly. Generating this necessary thrust for motion and acceleration is thoroughly affected by the vehicle aerodynamics. There is a lack of rigorous understanding of such topics owing to the immaturity of science in this area. Complexity and diversity of performance variables for a numerical solution and finding a logical connection between these parameters are among the related challenges.